The Identification of Students' and Teachers' Misconception on Energy in North Central Timor Regency - Muhammad Amran Shidik; Lidwina Felisima Tae (Jurnal Penelitian Pendidikan IPA, 2022)
This study aims to identify the misconception in the students as well as the teachers on the same topic, namely Energy. This study used mixed-method research of sequential exploratory type with the research subjects of the teachers and the students in North Central Timor Regency with a sample size of 163 students and 12 physics teachers. The misconception data was obtained by giving a misconception test in the form of a multiple-choice question. There were 12 questions with 5 answer choices which were equipped with CRI (Certainty of Response Index). The results showed that the percentage of students' misconceptions for the whole question (12 items) was quite large, namely 43.66%, while students who had a good understanding of the concept were 38.80%. Nearly 18% of students did not understand the concept while 4.24% were just guessing and lucky (Lucky Guess) while the remaining 13.29% were the total students who did not understand the concept of the questions at all. Meanwhile, of the teachers, an average of 77.08% have mastered the concept of Energy. However, as many as 22.92% of the teachers had the misconception on several questions, namely (question number 5,6,7,8,9,10, and 12) with the most misconceptions on question number 7, 10, and 5. The conclusion obtained was that the misconception found in physics teachers was 22.92%. For the students, there was still a large portion of them who had misconceptions about the topic of Energy. This was caused by the lack of students' understanding of the topic of Energy